MEASUREMENT OF SEDIMENT TRANSPORT USING AN OPTICAL BACKSCATTER SENSOR: CASE STUDY - CAN GIO MANGROVE FOREST, HO CHI MINH CITY - Cang, La Thi; Thanh, Nguyen Cong (Vietnam Journal of Marine Science and Technology, 2007)
OBS (Optical Back-Scattered Sensor) instrument is one of the most modern instrument used to measure the concentration of suspended sediment. The light scattering of the suspended matter in the water strongly correlates with the concentration as well as their sizes. Therefore, the reliability of the field data also depends strongly on the in-situ calibration. The calibrating procedures were carried out at Khe Oc creek, Can Gio mangrove forest, Ho Chi Minh city to convert the field data from OBS instrument (FTU unit) to the suspended sediment concentration (mg/1 unit) are presented as an example for this method.